Students’ Perception on the Use of QUILLBOT to Improve Grammar - Grégory Baron; Courtois Lorenzo; Dubois Benoît (Lingeduca: Journal of Language and Education Studies, 2023)
English structure is one of the most difficult parts of learning grammar. This is because students also have to know when to use it. When students already know the structure of English, it will be easier to master grammar. The easiest way to test students' grammar is by using the quillbot application. However, researchers using the quillbot application are still limited and know little about how students perceive it. This study aims to improve students' grammar skills by using quillbot application to check their grammar writing. The researcher used quantitative method and survey design, and to collect information the researcher used questionnaire. This study was conducted at University in Asia by taking a sample of 35 students majoring in English Department. The findings revealed that these students expressed some positive responses. Some students already know that this quillbot application can be relied upon to check students' grammar writing and make students easier and more practical in checking grammar so that it is free from grammatical errors. Therefore, the researcher said that the use of quillbot application is useful to improve students' grammar skills.